Methane and nitrous oxide production and their driving factors in Phragmites riparian wetlands of Dianchi Lake, China. (December 2022) - Li, Wei; Yuan, Lingchen; Lan, Xianli; Cui, Jingyi; Chen, Yue; Chen, Huai; Hu, Bin; Feng, Defeng
Highlights: The riparian wetlands of Dianchi Lake were the CH4 and N2 O production source. The CH4 and N2 O production rates differed significantly among the riparian zones of Dianchi Lake. The variation of CH4 production was mediated through soil AP, water NO3 − -N and mcrA abundance, while water NH4 + -N, Soil TN and NH4 + -N were the main factors regulating N2 O production in riparian wetlands of Dianchi Lake. Abstract: The eutrophic lake Dianchi, china, is a hotspot for methane (CH4 ) and nitrous oxide (N2 O) emissions. However, the potential factors driving CH4 and N2 O production in the riparian wetlands of Dianchi Lake remain unclear. In the current study, the potential CH4 and N2 O production was evaluated using incubation experiments. The abundance and community structure of the methanogenic communities and denitrifying bacteria were measured using quantitative polymerase chain reaction and Illumina MiSeq sequencing. The results indicated that the potential CH4 and N2 O production differed significantly among the riparian wetlands of Dianchi Lake, with rates of 0.26–17.65 μg/g.d and 0.09–1.30 ng/g.h, respectively. The soil mcrA, nirS and nosZ gene copies differed significantly among the riparian wetlands, whereas the soil narG and nirk genes did not. Soil methanogenic archaea in the riparian wetlands were dominated by the order Bathyarchaeia (2.36–45.97 %). Forty-one potential denitrifying bacterial genera were detected in soils from the riparian wetlands, among which the majority belonged to the Proteobacteria (31 genera; 1.54–37.78 %). The variation in CH4 production was mediated through soil AP, water NO3 − -N and soil mcrA abundance, while water NH4 + -N, soil TN and soil NH4 + -N were the main factors regulating N2 O production in the riparian wetlands of Dianchi Lake. Our study highlighted the important implication of pollution abatement to greenhouse gas emission reduction in the riparian wetland.